Reference Transcriptomes and Detection of Duplicated Copies in Hexaploid and Allododecaploid Spartina Species (Poaceae) - Boutte, Julien (Genome Biol Evol, 2016)
In this study, we report the assembly and annotation of five reference transcriptomes for the European hexaploid Spartina species (S. maritima, S. alterniflora and their homoploid hybrids S. x townsendii and S. x neyrautii) and the allododecaploid invasive species S. anglica. These transcriptomes were constructed from various leaf and root cDNA libraries that were sequenced using both Roche-454 and Illumina technologies. Considering the high ploidy levels of the Spartina genomes under study, and considering the absence of diploid reference genome and the need of an appropriate analytical strategy, we developed generic bioinformatics tools to (1) detect different haplotypes of each gene within each species and (2) assign a parental origin to haplotypes detected in the hexaploid hybrids and the neo-allopolyploid. The approach described here allows the detection of putative homeologs from sets of short reads. Synonymous substitution rate (K(S)) comparisons between haplotypes from the hexaploid species revealed the presence of one K(S) peak (likely resulting from the tetraploid duplication event). The procedure developed in this study can be applied for future differential gene expression or genomics experiments to study the fate of duplicated genes in the invasive allododecaploid S. anglica.